Optimalisasi Proses Bongkar Muat Minyak Produk di Dermaga Curah Cair PT. Pelindo III (Persero) Cabang Tanjung Emas Semarang - Fariz Mu’tasim; Meinina; Cahya Fajar Budi Hartanto (Politeknik Ilmu Pelayaran Semarang, 2021)
PT. Pelabuhan Indonesia III (Persero) branch of Tanjung Emas Semarang is a BUMN provider of port services. One of the services provided is the operation of ships at the port, such as loading and unloading activities. One of the loading and unloading activities is loading and unloading product oil at the liquid bulk dock. During the loading and unloading process of product oil, several obstacles or disruptions may occur which cause delays during the loading and unloading process, thus reducing the performance of the Port Business Entity. This study aims to determine the inhibiting factors originating from labor and other factors and to determine the efforts to overcome these obstacles. The method of data collection was carried out by observation or direct observation at the location for 3 months, interviews, and literature study. The results showed that the inhibiting factor of labor resulted in less optimal loading space and tank washing. In addition, the inhibiting factor also comes from damage to loading and unloading supporting equipment and bad weather conditions. This study provides recommendations for each inhibiting factor to be handled properly according to the procedure so that it is expected to provide positive results, namely the smooth loading of product oil at the liquid bulk dock of PT. Pelabuhan Indonesia III (Persero) Semarang branch of Tanjung Emas.